Tingkat Kebugaran Jasmani Adaptif Anak Berkebutuhan Khusus - Fitriatun, Erna; Susanto, Indri (Jurnal Ilmu Sosial dan Humaniora, 2023)
Adaptive physical fitness is a specialized method aimed at addressing challenges in the psychomotor domain specifically for children with exceptional needs. Special schools (SLB) are the designated locations for providing adapted physical education, alongside inclusive schools. This research was carried out in a specialized school (SLB) in West Lombok. The observations revealed that the school had never administered an adaptive physical fitness test for children with special needs. In addition, the participants in this study consisted of 20 children with special needs (ABK) who had hearing impairments, physical disabilities, and mental disabilities. Specifically, there were 17 males and 13 girls.  This study will employ the Euro fit exam, encompassing the Bent arm hang test, the sit and reach test, the 50-meter running test, the Flamingo balance test, and the Harvard step test. The majority of children with special needs at SLB Negeri 1 Lombok Barat had a low level of adaptive physical fitness, with 40% (12 children) falling into the "less" group. 60% (18 children) fall into the "moderate" category, while none of the children fall into the "good" category. These findings indicate that 60% of the children with special needs in the school fall into the intermediate category of physical fitness, which corresponds to a total of 18 children.